CEO Investment Cycles - Pan, Yihui; Wang, Tracy Yue; Weisbach, Michael S. (Review of Financial Studies, 2016)
This paper documents the existence of a CEO investment cycle, in which disinvestment decreases over a CEO's tenure, while investment increases, leading to “cyclical” firm growth in assets and employment. The estimated variation in investment rate over the CEO investment cycle is of the same order of magnitude as the differences caused by business cycles or financial constraints. Results from a number of tests generally support the view that the investment cycle is caused by agency problems, leading to increasing investment quantity and decreasing investment quality over time as the CEO gains more control over his board. Received February 17, 2015; accepted October 1, 2015 by Editor David Denis.